First Report of Forest Owlet Heteroglaux blewitti from Tansa Wildlife Sanctuary (Western Ghats), Maharashtra, India - Laad, Sunil; Dagale, Rohidas (Journal of the Bombay Natural History Society (JBNHS), 2014)
No abstract.